Driving cycle for small and medium duty engine case study of Ipoh - Ab Ghafar, Fauzi (2015)
Driving cycles is a series of data points representing the speed of vehicle verses time sequenced profile developed for certain road, route, specific area or city. It is widely used of application for vehicle manufacturers, environmentalists and traffic engineers. The purposes of this study are; to analyse the real world driving pattern and to develop a driving cycle for small and medium duty engines in Ipoh, Malaysia. This study carried out a survey to describe the motorcycle and car driving cycle on the selected three routes in the peak hour periods of the traffic condition, which are morning, afternoon and evening peak periods. The study used a GPS equipment to record vehicle travel speeds (second by second). The driving characteristics were analysed from speed time data and its target statistic parameters were defined. The method for generating the driving cycle has been described. The analysis results show that there are significant difference of driving characteristic and driving cycle between motorcycle and car for Ipoh city. The characteristic of the developed driving cycle for car was compared with three well established worldwide driving cycles. This information gives a clear message that those driving cycle such as ECE driving cycle (for instance) is not suitable to predict the emission standard in Ipoh. The driving cycle for motorcycle also had been compared with existing motorcycles driving cycles for Malaysia. It shows that the average speed of the developed Ipoh motorcycles driving cycle is higher than motorcycles driving cycle for Malaysia. The result clearly shows the driving cycle is dependent on specific area or city due to the different of traffic flow.